APPLICATION OF INHALATION THERAPEUTICS FOR LUNG CANCER TREATMENT: AN UPDATED REVIEW - NEHA, PADIYAR; TANUJA, BISHT; YOGITA, TYAGI; VIKAS, JHAKMOLA (International Journal of Applied Pharmaceutics, 2025)
Non-communicable Disease (NCDs) are the cause of around 71% of the total deaths globally. Lung cancer is one of the most common and serious malignancies throughout the world. According to the World Health Organization (WHO), lung cancer accounts for 2.2 million new cases annually, representing 11.7% of all cancer cases and 1.8 million deaths, representing approximately one-fifth of all cancer deaths, significantly more than those of breast cancer. The inhalational route for the delivery of drugs has received much attention in recent decades. This route can potentially increase and maintain drug concentration at the site of action. Targeting the chemotherapeutic agent leads to a decrease in dose and further decreases the systemic side effects. The pulmonary route also aids in reducing the drug dose variability due to its passage through the gastric environment. In this study, we have discussed various chemotherapeutic agents that exhibited better results when administered as micro-nanoparticles through an inhalational route. However, the delivery of drugs through inhalation also faces some challenges. The article reviewed all the barriers to inhalational therapy and the strategies to overcome these barriers.